Part II. Drama / Choreography1. Creative Approaches to Personal Development - Ciobotaru Anca Doina (Sciendo, 2017)
The contemporary Romanian school has frequently been a matter of debate; contents, methods, strategies, manuals, authors, analytical programs - they have all been supported, debated, annulled and reconsidered. However... The Ministerial Order that has allowed, in 2012, the introduction of "Personal Development" in the curriculum has opened a path that has not yet accomplished its role of guiding students to themselves and to the optimal variant for the manifestation of their potential; this aspect has even been demonstrated by analytical programs submitted to and edited by well known publishing houses. Therefore, the present study is meant to open an efficient dialog on the necessity of a transdisciplinary and creative approach to personal development.